Epidemiological profile of Tuberculosis in the State of Piauí located in Northeast Brazil between the years 2017 to 2021 (Research, Society and Development, 2023)
Tuberculosis is a contagious infectious disease, caused by Mycobacterium tuberculosis, being transmitted between contaminated patients through droplets of speech, sneezing or coughing that contain the bacillus. Tuberculosis is still a worldwide health problem, mainly due to its easy transmission, being considered one of the ten main causes of death in the world, according to the World Health Organization. The objective of this study was to analyze the numbers of notified cases of tuberculosis the State of Piauí located in Northeast Brazil in the years 2017 to 2021. It was an epidemiological, documental, quantitative, descriptive and retrospective study. Data were collected in the Notifiable Diseases Information System (SINAN), about all Tuberculosis cases confirmed in Piauí during the years 2017 to 2021. In the analyzed period, 4,053 cases were registered, with an annual average of 810.6/year. According to the results collected, the highest incidences were in male patients (65.2%), aged 20-39 years (35.5%). In addition, pulmonary tuberculosis was the main clinical form found, representing 83% of cases. As an extrapulmonary form, pleural tuberculosis (5.7%) was the most observed. The Mid-North Macroregion of the state of Piauí recorded the highest incidence of cases (57.9%). Thus, according to the results collected, it was possible to define the epidemiological profile of these patients and observe that social, economic and cultural factors can have a direct influence on the illness, treatment and recovery of patients.